1993
DOI: 10.1038/jcbfm.1993.37
|View full text |Cite
|
Sign up to set email alerts
|

Nonpeptide Angiotensin AT1 and AT2 Receptor Ligands Modulate the Upper Limit of Cerebral Blood Flow Autoregulation in Rats

Abstract: Summary:We investigated the effect of angiotensin AT! and AT2 receptor blockade on the upper limit of CBF autoregulation in pentobarbital-anesthetized rats. CBF was measured by laser-Doppler flowmetry from the pari etal cortex and MABP was increased by intravenous phenylephrine infusion. Neither the AT! antagonist 10-sartan nor the AT2 ligand PD 123319 nor angiotensin II (ANG II) in the presence of losartan affected baseline CBF. When the blood pressure was increased in the con trol group, CBF remained fairly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
1

Year Published

1994
1994
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 35 publications
0
22
1
Order By: Relevance
“…By contrast, the angiotensin II AT2 antagonist PD-123319 in our laboratory did not influence the lower limit of autoregulation in SHR (5). Other studies of the effect of the AT1 antagonist losartan and PD-123319 have given somewhat contradictory results, and it is possible that these antagonists may display angiotensin receptor agonist activity (15,25,26).…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…By contrast, the angiotensin II AT2 antagonist PD-123319 in our laboratory did not influence the lower limit of autoregulation in SHR (5). Other studies of the effect of the AT1 antagonist losartan and PD-123319 have given somewhat contradictory results, and it is possible that these antagonists may display angiotensin receptor agonist activity (15,25,26).…”
Section: Discussioncontrasting
confidence: 55%
“…Blockade of the reninangiotensin system by angiotensin-converting enzyme (ACE) inhibitors, e.g., captopril (2, 3, 30), shifts both the lower and upper limits of CBF autoregulation toward lower blood pressure, possibly by releasing angiotensin II-mediated tone in the larger cerebral resistance vessels (21), with a contribution of bradykinin accumulation (27). Angiotensin II subtype 1 (AT1) receptor antagonists and agonists also shift the limits of CBF autoregulation (15,26,33). Modulation of the angiotensin II AT2 receptors appears to have limited influence on CBF autoregulation (5, 15, 26).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, Strömberg and co-workers showed that PD 123319 and losartan, an ARB, both shifted the upper limit of CBF autoregulation towards higher BP. 6,7 They suggested that stimulation of the AT 2 -receptor causes vasoconstriction, and that vasodilation is mediated through the AT 1 -receptor. According to these studies, PD 123319 functions as an agonist at the AT 2 -receptor, causing vasoconstriction, and losartan acts as an antagonist at the AT 1 -receptor, also causing vasoconstriction, resulting in a shift of the upper limit of autoregulation towards higher BP.…”
Section: Discussionmentioning
confidence: 99%